Analisis Perubahan Respons Amerika Serikat Terhadap Ancaman Terorisme Islam: Desekuritisasi Periode Obama - Wiratmini, Ni Putu Eka; Sushanti, Sukma; Kawitri Resen, Putu Titah (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT The process of desecuritization of Islamic terrorism becomes an interesting thing to be studied in the study of International Relations. This study attempted to analyze the process of Obama in conducting the desecuritization of terrorism through his speech to the Islamic community and the world. The research used descriptive qualitative research method with two concepts, namely: speech act from Nicholus Onuf which is explain the built process of rules through language construction and desecuritization by Barry Buzan that’s explain how threats transfer into the public sphere. Both concepts can help to analyze the process of Obama conducting Islamic terrorism desecuritization. This desexuritization is related to Obama identity that’s close by the culture and environment of third world countries. This makes him have a better understanding of Islam than his predecessor. The analytical technique used in this study is to interpret the data through focusing Obama's discourse or speech. Keywords: Terrorism, Desecuritization, Speech Act, United States